A matemática e o futebol: aprendendo matemática com as cobranças de pênaltis - Zola, Fausto Lombardo (2018)
In this work, having as a guideline the football penalty kicks, is presented the idealization, the development, the application and the results analysis of a didactic sequence in order to teach and recover some mathematical concepts. As final product a penalty simulator in GeoGebra and five activity sheets were obtained, which were applied in two classes of the second year of high school in a private school in Bebedouro/SP.